2022
DOI: 10.21203/rs.3.rs-2280166/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevation Determines the Productivity of Large Cardamom (Amomum subulatum Roxb.) Cultivars in Sikkim Himalaya

Abstract: Large cardamom (Amomum subulatum Roxb.) is an economically important cash crop that provides a livelihood option for the rural communities in the Khangchendzonga Landscape (KL), including Sikkim and supports a large value-chain of diverse stakeholders across the globe. This study explores the influence of elevation on yield-related traits of the large cardamom cultivars grown at different elevations in Sikkim. We evaluated twelve morphometric traits, including eight yield-related traits (number of capsules per… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…In the Nordic region (Northern Europe), the distribution of cereal and grass is likely to shift by up to 92.8 and 178.7 km, depending on the intensity of climate change [71], and some crop species have already been introduced to new areas [72]. Our study on large cardamom (Amomum subulatum Roxb., a commercially important spice crop of Sikkim, India) also indicated that cultivars previously grown at low elevations (below 975 m asl) are shifted to high elevations (above 975 m), and climate change is augmenting this elevational shift [73].…”
Section: Climate Change Causing Habitat Shiftsmentioning
confidence: 99%
“…In the Nordic region (Northern Europe), the distribution of cereal and grass is likely to shift by up to 92.8 and 178.7 km, depending on the intensity of climate change [71], and some crop species have already been introduced to new areas [72]. Our study on large cardamom (Amomum subulatum Roxb., a commercially important spice crop of Sikkim, India) also indicated that cultivars previously grown at low elevations (below 975 m asl) are shifted to high elevations (above 975 m), and climate change is augmenting this elevational shift [73].…”
Section: Climate Change Causing Habitat Shiftsmentioning
confidence: 99%
“…1. nettle fibre traditional water retting yarn making process [4] performance, the minimum ratio of nettle bark weight in kg to liquid water volume in litter should be maintained at 1:30. The processed ribbons were then removed from the non-fibrous material and sun dried for 48 hours at 37°C [10].…”
Section: Water Degumming Nettle Fibre Extractionmentioning
confidence: 99%
“…The nettle bark was fully dried after the pre-treatment. To get optimum performance, maintain a constant ratio of plant material weight in kg to liquid volume in litter of 1:30 by volume [3][4][5][6]. The nettle bark was treated with 1500 ml of 1% (W/v) sodium hydroxide,0.5% (W/v) sodium sulphite, and 0.05% (W/v) ethylenediaminetetraacetic acid, and the pH value was maintained at 10-10.5 in the naOH solution (10 g sodium hydroxide per 1000 ml of water) [15][16].…”
Section: Chemical Treated Nettle Fibre Extractionmentioning
confidence: 99%
See 2 more Smart Citations